Highly selective and ultra-sensitive electrochemical sensor behavior of 3D SWCNT-BODIPY hybrid material for eserine detection - KOCA, ATIF (ELSEVIER ADVANCED TECHNOLOGY, 2019)
In this work, 4,4-difluoro-8-(4-hydroxyphenyl) - 2,6-diethynly-1,3,5,7-tetramethyl-4-bora-3a,4a-diaza-s-indacene (BODIPY) having double terminal ethynyl groups was synthesized. Three dimensional single walled carbon nanotube (SWCNT)-BODIPY hybrid material (3D SWCNT-BODIPY) was synthesized by the reaction of BODIPY bearing double terminal ethynyl groups with azido containing SWCNTs via Click reaction. The structural properties and electrochemical detection of eserine (a pesticide) on BODIPY functionalized SWCNTs as a three dimensional (3D) material were investigated. A glassy carbon electrode (GCE) was modified by 3D SWCNT-BODIPY hybrid material for the determination of eserine in the range of 0.25-2.25 M. In the study by the square wave voltammetry (SWV), the bare GCE showed no response, while the new peak at - 0.6 V appeared in the case of the modified electrode. The detection limit and quantification were determined as 160 nM and 528 nM for eserine on the 3D SWCNT-BODIPY modified electrode, respectively. Eserine was also determined with a standard addition method in different brands of orange juices, and the recovery of eserine was obtained to be in the range of 102.09% and 103.22%. This study clearly indicates that the 3D SWCNT-BODIPY modified electrode tested as an electrochemical sensor was found to be highly selective and sensitive to eserine.
Keywords: Eserine sensor; Pesticide; Click reaction; 3D hybrid; BODIPY; SWCNT; CARBON; ACETYLCHOLINESTERASE; NANOMATERIALS; PESTICIDES; PERFORMANCE; COVALENT; DESIGN; FOOD